Biochemical characterization of recombinant influenza A polymerase heterotrimer complex: Endonuclease activity and evaluation of inhibitors. - Weimei Xing; Ona Barauskas; Thorsten Kirschberg; Anita Niedziela-Majka; Michael Clarke; Gabriel Birkus; Perry Weissburg; Xiaohong Liu; Brian E Schultz; Roman Sakowicz; HyockJoo Kwon; Joy Y Feng (PLoS ONE, 2017)
Influenza polymerase is a heterotrimer composed of polymerase acidic protein A (PA) and basic proteins 1 (PB1) and 2 (PB2). The endonuclease active site, located in the PA subunit, cleaves host mRNA to prime viral mRNA transcription, and is essential for viral replication. To date, the human influenza A endonuclease activity has only been studied on the truncated active-site containing N-terminal domain of PA (PAN) or full-length PA in the absence of PB1 or PB2. In this study, we characterized the endonuclease activity of recombinant proteins of influenza A/PR8 containing full length PA, PA/PB1 dimer, and PA/PB1/PB2 trimer, observing 8.3-, 265-, and 142-fold higher activity than PAN, respectively. Using the PA/PB1/PB2 trimer, we developed a robust endonuclease assay with a synthetic fluorogenic RNA substrate. The observed Km (150 ± 11 nM) and kcat [(1.4 ± 0.2) x 10-3s-1] values were consistent with previous reports using virion-derived replication complex. Two known influenza endonuclease phenylbutanoic acid inhibitors showed IC50 values of 10-20 nM, demonstrating the utility of this system for future high throughput screening.